Neutron spectra around a tandem linear accelerator in the generation of 18F with a bonner sphere spectrometer. (August 2016) - Lagares, J.I.; Araque, J.E. Guerrero; Méndez-Villafañe, R.; Arce, P.; Sansaloni, F.; Vela, O.; Díaz, C.; Campo, Xandra; Pérez, J.M.
Abstract: A Bonner sphere spectrometer was used to measure the neutron spectra produced at the collision of protons with an H2 18 O target at different angles. A unique H2 18 O target to produce 18 F was designed and placed in a Tandem linear particle accelerator which produces 8.5 MeV protons. The neutron count rates measured with the Bonner spheres were unfolded with the MAXED code. With the GEANT4 Monte Carlo code the neutron spectrum induced in the (p, n) reaction was estimated, this spectrum was used as initial guess during unfolding. Although the cross section of the reaction 18 O(p, n) 18 F is well known, the neutron energy spectra is not correctly defined and it is necessary to verify the simulation with measurements. For this reason, the sensitivity of the unfolding method to the initial spectrum was analyzed applying small variation to the fast neutron peak. Highlights: A neutron spectrum has been measured in a real target used in a 18 F production cyclotron. Angular dependence of neutron emission rates in p( 18 O, 18 F)n agrees with literature. Spectra obtained with Geant4 Monte Carlo using TENDL-2010 library disagree with experiment.